Clima e saúde: relações entre os elementos atmosféricos e a dengue na região metropolitana de Fortaleza - Magalhães, Gledson Bezerra (2011)
The aim of this work consists at analyzing the manifestation of “dengue” at Metropolitan Region of Fortaleza between the years 2001 to 2009, relating the number of cases and incidences of the disease with the infestation of its principal vector and the climatic characteristics of the region. So, were purchased rainfall data, air temperature, the larval infestation of the mosquito Aedes aegypti, the number of cases and incidence of dengue. It was crafted maps, charts and statistical correlations that were established between the variables. It was verified a behavior of spatially and temporally heterogeneous rains, but it was similar each year. Over the years with large amounts of rain and homogeneity of precipitation in the rainy court, the highest number of cases of dengue occurred one to two months after the large rainfall totals, which is not the case in years with low rainfall where the greatest amount of Dengue cases occurred both in the month with the highest total rainfall as in other months they had succeeded or within 2 months the rainfall peaks. In years when there were few cases of dengue, there was a spatial and temporal randomness of their cases, and apparently lower connection with the atmospheric elements. In epidemic years, there is a clearer monthly relationship between number of cases and precipitation as well as a greater temporal similarity in the behavior of dengue among the municipalities. It was not identified relationships between the monthly temperature variations with cases of dengue and Aedes aegypti infestation, however it was noted that minimum, mean and maximum temperatures favor the spread of disease. In despite of the correlations between air temperature and dengue cases show negative results, it can not be said that the lower temperatures favor the increase of dengue cases more than maximum temperatures, due to the fact that other factors, such as precipitation, have a greater influence on the spread of the disease.